BUDAYA RELIGIUS SEKOLAH DASAR DI PULAU JAWA Studi Sekolah Dasar Negeri 1 Pasirkaliki Cimahi dan Sekolah Dasar Hj. Isriati Baiturrahman 1 Semarang dalam Menciptakan Peserta Didik yang Berbudi Pekerti Luhur dan Berprestasi Hasil Belajar - R Agus Abikusna; Suhatma Suhatma (IAIN Syekh Nurjati Cirebon, 2019)
AbstractAccording to the mandate of the Act, education is to develop character and achievement holistically. It seems that this educational goal does not reach expectations. It can be seen from the rise of elementary school students’ moral decadence. In addition, learning achievement is still lagging when compared in a global context. This condition is quite apprehensive. Therefore, it is necessary to create a religious culture. There are interesting things, however, that happen in State Primary School Pasirkaliki 1 Cimahi and Primary School Hj. Isriati Baiturrahman 1 Semarang. Both schools create a religious culture and implicate good manners and achievement of student learning outcomes. This research is based on Lickona's theory. The research method is qualitative descriptive. The instruments are in-depth interviews, in-depth observation, and documentation. The analysis is conducted through data collection, data reduction, data display, and data conclusion. The research findings show that (1) students’ religious culture and good character in elementary education in Java Island both in State Primary School Pasirkaliki 1 Cimahi and Primary School Hj. Isriati Baiturrahman 1 Semarang already be implemented well so, generally, it creats students’ good character. (2) Student achievement of primary education in Java Island, State Primary School Pasirkaliki 1 Cimahi and Primary School Hj. Isriati Baiturrahman 1 Semarang, is excellent and the best in their region. (3) State Primary School Pasirkaliki 1 Cimahi and Primary School Hj. Isriati Baiturrahman 1 Semarang do many efforts in creating a religious culture and outstanding students. Nevertheless, these efforts are quite consistent and serious in the frame of habituation and exemplary to learners. (4) The headmaster of State Primary School Pasirkaliki 1 Cimahi has performed formally her role, and less active when compared with her role subordinate (a teacher). This means that the role of leadership seems to be taken over by this teacher. Meanwhile, the role of school principal Primary School Hj. Isriati Baiturrahman 1 Semarang is quite good and dominant. He became the mover of his subordinates in creating a school religious culture.Keywords: Culture, Religious, Character, Achievement